1980
DOI: 10.1002/j.2050-0416.1980.tb06881.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Biochemical Composition of Acid Extracts From Barleys of Contrasting Malting Quality

Abstract: Acid extracts from barleys of poor malting quality were characterized by high viscosity caused by enhanced concentrations of high molecular weight carbohydrates of which more than 80 per cent was /7-glucan. Up to 67 per cent of the j3-glucan in these barleys was soluble in the acid extract ing solution. In contrast, only about 25 per cent of the /3-glucan in good malting barleys was soluble, resulting in extracts having low viscosity. No evidence was found for autolysis in any of the extracts, and extracts fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…Two (M-737, M-1460) were low in total I~-glucan content, while the others (M-699, M-892) contained relatively high levels of total lS-glucan, confirming the earlier observations that the ratio of soluble to total 13-glucan in barley varieties can vary significantly (2,3,29). The reason for this is uncertain, but it is apparent that little or no 13-glucan soluble at pH 1.5 is synthesised in the four mutant lines.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Two (M-737, M-1460) were low in total I~-glucan content, while the others (M-699, M-892) contained relatively high levels of total lS-glucan, confirming the earlier observations that the ratio of soluble to total 13-glucan in barley varieties can vary significantly (2,3,29). The reason for this is uncertain, but it is apparent that little or no 13-glucan soluble at pH 1.5 is synthesised in the four mutant lines.…”
Section: Discussionsupporting
confidence: 84%
“…A low viscosity of acid extracts of barley flours has been shown to indicate low [3-glucan content and good malting quality (2,15,24), although the overall correlation between viscosity of acid extract and total ~-glucan is poor (2,29). In the present study, however, a quick screening method based on barley extract viscosity (2) was used successfully in the search for low ~-glucan mutants of the high 13-glucan barley variety, Minerva.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Recent studies reported that an interesting feature of the composition of malt extracts is the very small variation in the total carbohydrate concentration, particularly for the hexose sugars where the large variation in β-glucan and starch content is offset by differences in the concentration of simple sugars (Smith and Morgan 1980). These sugars are principally fructose, sucrose and glucose, and it has been suggested that the concentrations are highest in extracts from the better malting varieties (Smith and Morgan 1980;Cozzolino et al 2014a, b).…”
Section: Grain and Malt Samplesmentioning
confidence: 96%
“…SMITH et al (20) suggested that the ratio between the HMW and the LMW carbohydrate fraction from acid extracts of barley flour could disclose the malting potential of a barley genotype. Our results show a similar distinction, i.e.…”
Section: Discussionmentioning
confidence: 99%